Prevention and rescue of cardiac dysfunction by methanocarba adenosine monophosphonate derivatives - Shen, Jian-Bing (Purinergic Signal, 2020)
Accumulating evidence supports a therapeutic role of purinergic signaling in cardiac diseases. Previously, efficacy of systemically infused MRS2339, a charged methanocarba derivative of 2-Cl-adenosine monophosphate, was demonstrated in animal models of heart failure. We now test the hypothesis that an uncharged adenine nucleoside phosphonate, suitable as an oral agent with a hydrolysis-resistant phospho moiety, can prevent the development of cardiac dysfunction in a post-infarction ischemic or pressure overload-induced heart failure model in mice. The diester-masked uncharged phosphonate MRS2978 was efficacious in preventing cardiac dysfunction with improved left ventricular (LV) fractional shortening when administered orally at the onset of ischemic or pressure overload-induced heart failure. MRS2925, the charged, unmasked MRS2978 analog, prevented heart dysfunction when infused subcutaneously but not by oral gavage. When administered orally or systemically, MRS2978 but not MRS2925 could also rescue established cardiac dysfunction in both ischemic and pressure overload heart failure models. The diester-masked phosphate MRS4074 was highly efficacious at preventing the development of dysfunction as well as in rescuing pressure overload-induced and ischemic heart failure. MRS2978 was orally bioavailable (57–75%) giving rise to MRS2925 as a minor metabolite in vivo, tested in rats. The data are consistent with a novel therapeutic role of adenine nucleoside phosphonates in systolic heart failure. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s11302-020-09688-0) contains supplementary material, which is available to authorized users.